Influence of water content, concentration, and nutrient addition on the biofiltration of toluene for air pollution mitigation using soil biofilters with water content control - Badilla, Daisy B. (2011.)
In this study on biofiltration as an air pollution control technology, three laboratory-scale biofilters with water content control were used to treat toluene-contaminated air with soil as the biofilter bed medium. The microorganisms in the biofilter medium degrade and convert the toluene to water, carbon dioxide, and biomass. Thus, biofiltration is often favored over other air pollution control technologies since it does not produce secondary pollutants. It also does not involve expensive maintenance and operating costs. However, one of its disadvantages is the problem on water content control.
Improving biofiltration involves increasing the degradation capabilities of the microorganisms by providing the needed optimum condition, and understanding inhibiting conditions and critical controllers of biofiltration. This study investigates three controlling factors in the operation of biofilters namely water content, concentration, and nutrients.
A water retention curve of the soil used as the medium in the biofilter was generated from the data obtained using the suction cell which controls water content in this study. Identifying the air-entry value in the water retention curve is very important as it points to the optimum water content which gives the highest elimination capacity.
The experiments on water content, concentration, and nutrient addition are intended to get results that may help attain the goal of this study which is to contribute to improving biofiltration performance through relevant conclusions and recommendations that may guide biofiltration operation, broaden concepts, and direct future studies. Application of biofiltration for indoor air pollution control is considered.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Toluene; Air -- Purification; Air quality management